The Effect of Using Quizlet on Students’ Vocabulary Achievement - Endriyatin Endriyatin; Sahlan Sahlan; Tambunan Tambunan (Journal of Language Education and Educational Technology (JLEET), 2021)
The present research is concerned with the effect of Quizlet on students’ vocabulary achievement and perception. A quasi experimental research design was employed, involving a control group and an experimental group. Each group consisted of thirty students. The sample of the study was determined by way of purposive sampling. The only difference between the control group and the experimental one was that the latter was taught using Quizlet, whereas the former was not. Two types of instruments were used: a vocabulary test and a questionnaire. The findings of the research show that the experimental group outperformed the control group and that students had a positive perception on the use of Quizlet for learning vocabulary.Keywords:Quizlet, vocabulary achievement, Perception on Quizlet